Solve the equation 5t-3=18+3(1-1t)

5t-3=18+3\left(1-t\right)

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$t=3$

Step by step solution

Problem

$5t-3=18+3\left(1-t\right)$
1

Multiply $\left(1+-t\right)$ by $3$

$5t-3=18-3t+3$
2

Add the values $3$ and $18$

$5t-3=21-3t$
3

Grouping terms

$3t-3+5t=21$
4

Adding $5t$ and $3t$

$8t-3=21$
5

Subtract $-3$ from both sides of the equation

$8t=3+21$
6

Add the values $21$ and $3$

$8t=24$
7

Multiply both sides of the equation by $$

$t=3$

Answer

$t=3$

Problem Analysis

Main topic:

Polynomials

Time to solve it:

0.25 seconds

Views:

99